Perbandingan Terapi Peeling Kimiawi Dengan Glycolic Acid 35% dan Mandelic Acid 30% dalam Menurunkan Derajat Keparahan Akne Vulgaris - Mellaratna, Wizar Putri; Millizia, Anna; Nurfitri Erida, Bela; Nurul Tasha, Ghina (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2023)
Introduction: Acne vulgaris is a pilosebaceous unit disorder which is mostly seen in adolescents and adults with approximately 85% occurs at the age of 12-25 years. Methods: The purpose of this study is to know the comparison between chemical peeling therapy with 35% glycolic acids (GA) and 30% mandelic acids (MA) to reduce the severity of acne vulgaris. A total of 30 medical students suffering from mild to severe acne vulgaris were involved in this study. The patients were randomly divided into two groups, with one group receiving 35% GA and the other group receiving 30% MA peels at an interval of 4 weeks for two sessions. The Mann Whitney test is used to analysis the difference between chemical peeling therapy with 35% GA and 30% MA to reduce the severity of acne vulgaris. The p value < 0,05 is considered statistically significant. Results and discussion: majority of the patients are females (70,0%), age 14 years olds (50,0%), duration of acne vulgaris 7,8 and 10 years (16,7%). There is no significant difference between 35% GA and 30% MA in reducing the severity of acne vulgaris (p > 0,05). Chemical peels with MA has an antibacterial effect and is used to treat others skin disorders such as acne, photoaging, and pigmentation disorders. GA peels is proven to be effective in the treatment of inflammation and non-inflammation acne. Conclusions: there is no difference between chemical peels with 35% GA and 30% MA in reducing the severity of acne vulgaris. Keywords: acne vulgaris; chemicals peels, treatment, severity of acne